The influence of moisturizer co-application protocols on In vitro penetration of betamethasone in porcine skin - Rost, Daiane Luiza (2025)
Background/Objectives: The treatment of atopic dermatitis frequently involves using a topical corticosteroid and a moisturizer. While the sequential application of these products is a common dermatological practice, their influence on drug penetration remains poorly understood. There is no clear evidence on how hydration, application sequence, and massage affect cutaneous drug delivery. Hence, this study aimed to evaluate the effects of formulation type, moisturizer composition, application sequence, and mechanical stimulation on betamethasone dipropionate (BET) cutaneous penetration. Methods: Two commercial formulations (cream and ointment) of BET were evaluated in different experimental conditions, including drug application combined with moisturizers (Cetaphil®, as an emollient; Nivea®, as an occlusive) pre- or post-application, with or without a 30 s massage. In vitro skin penetration assays were conducted for 12 h using porcine skin mounted in modified Franz diffusion cells. BET levels were extracted from the skin layers and quantified by HPLC. Results: The cutaneous BET penetration was strongly influenced by the application sequence, type of moisturizer, and mechanical stimuli. Pre-application of an occlusive or emollient moisturizer, followed by 30 s physical stimuli, significantly enhanced drug retention in the stratum corneum. For the cream, pre-application of moisturizers followed by massage notably increased BET levels in both the stratum corneum and viable skin. Conversely, post-application of moisturizers hindered BET absorption. The ointment showed limited penetration across all conditions, with no drug detected in the viable skin. Conclusions: The results showed pre-hydrating the skin, combined with a 30 s massage, was the best strategy for BET diffusion into the skin following cream administration. The formulation type and the order of application directly influence the effectiveness of drug therapy and the topical absorption of BET.